Central Bank-Led Fintech Competition and Bank Digital Transformation in Cambodia: Evidence from Bakong, Khqr, and Interoperable Payment Infrastructure: Evidence From Bakong, Khqr, and Interoperable Payment Infrastructure - Sam Ean Lay; Vuddneath Som; Sothearak; Sophat Phon; Pidor Ngin (PT SOLUSI EDUKASI BERDIKARI, 2026)
This article examines how fintech competition has reshaped financial intermediation in Cambodia and how incumbent commercial banks have responded to central-bank-led interoperable payment infrastructure. Using a qualitative explanatory case-study design and documentary analysis of policy documents, official payment-system statistics, institutional reports, and peer-reviewed research, the study analyzes Bakong, KHQR, and the broader digital payments ecosystem as public infrastructure shaping private financial-sector transformation. The findings show that Cambodia’s fintech evolution is better understood as state-enabled restructuring of the competitive field than as simple displacement of banks by fintech entrants. By the end of 2023, Cambodia recorded 19.7 million e-wallet accounts, 601.3 million payment-service-provider transactions, and USD 75.8 billion in payment-service value, while Bakong had 74 members, approximately 19.5 million connected accounts, and 200.93 million cumulative transactions. The Cambodian case demonstrates that public payment rails can intensify competition while reducing fragmentation, but sustainable gains depend on financial literacy, cybersecurity, data governance, institutional capability, and proportionate regulation.